Financiamento público ao sistema setorial de inovação farmacêutico brasileiro - Luiza Pinheiro Alves da Silva (2015)
The objective of this paper is to present the Brazilian sectoral system of pharmaceutical innovation, with emphasis on the subsystem of public financing and the innovative efforts of pharmaceutical companies. Such system is presented, through the description of the pharmaceutical innovation process and a detailed description of each of its actors and their role is given. An analysis of the public financing for the Brazilian pharmaceutical innovation system is made, from an overview of the instruments used for investment in this sector, in addition to the allocation of resources for pharmaceutical innovation system. It is also analyzed the alignment between actions that encourage development of innovative technologies and the incorporation of such technologies in the Brazilian public health system. Finally, it is shown the innovative efforts of the Brazilian pharmaceutical companies, by analyzing the results of the Innovation Survey (PINTEC) of IBGE and a comparative analysis of the patenting activity of some companies that received some form of federal government funding. The conclusion is that the information available about the public financing instruments for innovation is unclear and scattered. Historically, the health area has received public resources for investment in innovation. It is observed that Brazilian companies mainly perform incremental innovations in the country. This reflects the adoption of a cautious innovation strategy that, although it has been very important to ensure the success of these companies in the significant market for generic drugs, is not enough to bring them closer to the forefront of the technological frontier in this industry. Nonetheless, it is important to note through a change in the allocation of expenditures in R,D & I of the Brazilian pharmaceutical firms a move towards more advanced innovative activities.